2015
DOI: 10.1016/j.im.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Massively multiplayer online game addiction: Instrument development and validation

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 89 publications
(90 reference statements)
0
27
0
Order By: Relevance
“…[Please insert Convergent validity relates to the extent to which the items of an instrument appear to be indicators of a single underlying construct (Lee, Cheung, & Chan, 2015).…”
Section: Factorial Validity: Confirmatory Factor Analysis (Cfa)mentioning
confidence: 99%
See 1 more Smart Citation
“…[Please insert Convergent validity relates to the extent to which the items of an instrument appear to be indicators of a single underlying construct (Lee, Cheung, & Chan, 2015).…”
Section: Factorial Validity: Confirmatory Factor Analysis (Cfa)mentioning
confidence: 99%
“…Additionally, discriminant validity refers to the degree to which the measures of distinct constructs differ (Lee et al, 2015), and can be demonstrated when the square root of the AVE for each construct is higher than the correlations between it and the rest of the constructs (Fornell & Larcker, 1981;Hair et al, 2010). The square root of the AVE for each construct is shown in Table 3 (located in bold on the diagonal of the table).…”
Section: Factorial Validity: Confirmatory Factor Analysis (Cfa)mentioning
confidence: 99%
“…With the emergence of new technologies such as smart homes, smart cars, fitness trackers, drones, and virtual reality (e.g., Wilson et al 2015) and the continued rise of established technologies such as social media sites or massive multiplayer videogames (e.g., Cheung et al 2011;Lee et al 2015), a new paradigm of heavily digitized individuals has developed (Qahri-Saremi and Turel 2016;Thompson 2013;Vaghefi et al 2017;Vodanovich et al 2010). The increased use of devices and services calls for a deeper, contextualized understanding of how digital technologies shape individuals' behaviors and interactions, and what consequences such developments entail for individuals, organizations, and society.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [33], Beranuy et al [34] and Griffiths [35] argue that there are core components a player needs to experience to get addicted to a video game. Those are salienceoccurs when playing dominates a person's thinking, feelings and behavior and becomes the most important activity in his or her life -, mood modification -when the players' game experience is a way of dealing or escaping from other areas on their life -, toleranceif a player increase the amount of time in the game due to mood modification effects, it leads to tolerance -, withdrawal symptoms feeling states or physical effects that players experience when they are not able to play -, conflict -occurs when playing too much time starts to interfere with players' livesand relapse happens if, when trying to change behavior and reduce playing time, the previous behavior is quickly restored.…”
Section: Motivation To Play Mmogsmentioning
confidence: 99%